Melatonin alleviates low-sulfur stress by promoting sulfur homeostasis in tomato plants - Hasan, Md. Kamrul (Sci Rep, 2018)
Despite involvement of melatonin (MT) in plant growth and stress tolerance, its role in sulfur (S) acquisition and assimilation remains unclear. Here we report that low-S conditions cause serious growth inhibition by reducing chlorophyll content, photosynthesis and biomass accumulation. S deficiency evoked oxidative stress leading to the cell structural alterations and DNA damage. In contrast, MT supplementation to the S-deprived plants resulted in a significant diminution in reactive oxygen species (ROS) accumulation, thereby mitigating S deficiency-induced damages to cellular macromolecules and ultrastructures. Moreover, MT promoted S uptake and assimilation by regulating the expression of genes encoding enzymes involved in S transport and metabolism. MT also protected cells from ROS-induced damage by regulating 2-cysteine peroxiredoxin and biosynthesis of S-compounds. These results provide strong evidence that MT can enhance plant tolerance to low-S-induced stress by improving S uptake, metabolism and redox homeostasis, and thus advocating beneficial effects of MT on increasing the sulfur utilization efficiency.